Occupational hazard for Dental staff exposed to the SARS-CoV-2 virus during Dental procedures - Burić Nina; Stojanović Simona (Medicinski fakultet i Klinika za stomatologiju, Niš, 2020)
Introduction: The dental profession is a high-risk profession, considering the aspect of a possible 100% infection from patients who are carriers of bacterial, viral and fungal diseases during dental interventions. Aim: To perform the analysis of all data that explain the possibility of a SARS-CoV-2 virus infection in dental practice. Material and Methods: The literature data on the presence of SARS-CoV-2 virus, and its characteristics and behavior in the external environment and in living tissues was analyzed. Databases from the Medline, Cochrane Library, Science-Direct, EMBASE, and Google scholar libraries were used, as well as other sources of literature information about this virus. Results: SARS-CoV-2 is an RNA virus, which has a submicron size and the ability to survive in various environments. The retention of SARS-CoV-2 virus in air / aerosol lasts an average of 3 hours, while the half-life of this virus is 5 to 6 hours on stainless steel and 6 to 8 hours on plastic. Infected patients with SARS-CoV-2 virus develop COVID-19 disease, which manifests itself through presymptomatic, symptomatic and post-symptomatic periods of the disease. Conclusion: The SARS-CoV-2 virus can be found in aerosols generated by dental equipment, which uses compressed air for its work. Protection of dentists and staff from infection with the virus is possible by wearing an N95 respiratory mask with protection levels 2 and 3, which has a filtration efficiency, i.e. retention of submicron particles with an efficiency of ≥ 98%. Waterproof goggles with a protective visor or a special industrially designed facial visor in the form of a full face mask, which has its own motor for the supply of filtered air to the mask, and which prevents the contamination of the mucous membranes of the eyes, nose and mouth from liquid or solid aerosol in the air, need to be used. Other disposable protective equipment also must be waterproof. Korona virus izaziva prehladu kod ljudi, koja ima uobičajne simptome prehlade gornjih respiratornih puteva; zahvata nosnu šupljinu,a ponekad se širi i na ždrelo, larinks i sinuse 5,6,7 . Sa druge strane, SARS-CoV-2 virus, koji je izazivač masovne/globalne virusne infekcije, ima sličnosti sa druga dva korona virusa -beta korona virusom (SARS-CoV-1) i virusom srednjeistočnog respiratonog sindroma (MERS-CoV).